Load Carrying Capacity of High Strength Cold-Formed Steel Built-Up Box Sections - Lau, Hieng Ho; Ting, Chui Huon (Research Publishing Services, 2010)
This paper presents an experimental study of the cold-formed steel built-up box sections in compression. The built-up box sections are formed by two identical simple C-lipped channels connected at their flanges with self-drilling screws. The specimens were compressed between fixed end conditions for stub columns and also for intermediate columns. The column test strengths were compared with the theoretical design strengths, which were calculated using the Effective Width Method (EWM) and also the Direct Strength Method (DSM). Three analytical models were proposed for the compressive strength prediction of the built-up box section. Results from the study show that Effective Width Method predicts the compressive strength of built-up box sections better than Direct Strength Method. Proposed analytical model 1 results for stub columns and model 2 results for intermediate columns correlates well with the experimental results.